A functionally dominant mitochondrial DNA mutation - Sacconi, Sabrina (Oxford University Press, 2008)
Mutations in mitochondrial DNA (mtDNA) tRNA genes can be considered functionally recessive because they result in a clinical or biochemical phenotype only when the percentage of mutant molecules exceeds a critical threshold value, in the range of 70–90%. We report a novel mtDNA mutation that contradicts this rule, since it caused a severe multisystem disorder and respiratory chain (RC) deficiency even at low levels of heteroplasmy. We studied a 13-year-old boy with clinical, radiological and biochemical evidence of a mitochondrial disorder. We detected a novel heteroplasmic C>T mutation at nucleotide 5545 of mtDNA, which was present at unusually low levels (<25%) in affected tissues. The pathogenic threshold for the mutation in cybrids was between 4 and 8%, implying a dominant mechanism of action. The mutation affects the central base of the anticodon triplet of tRNA(Trp) and it may alter the codon specificity of the affected tRNA. These findings introduce the concept of dominance in mitochondrial genetics and pose new diagnostic challenges, because such mutations may easily escape detection. Moreover, similar mutations arising stochastically and accumulating in a minority of mtDNA molecules during the aging process may severely impair RC function in cells.